KADAR GLUKOSA DARAH ANJING KAMPUNG (Canis familiaris) SEBELUM DAN SESUDAH BERBURU DI KENAGARIAN MUNGO KECAMATAN LUAK KABUPATEN LIMA PULUH KOTA PROVINSI SUMATERA BARAT (Blood Glucose Levels of Dogs (Canis familiaris) Pre and Post Hunting in Kenagarian Mungo, Luak, Lima Puluh Kota, and West Sumatera) - Alkhalidri Murfi; Zuhrawati Zuhrawati; Sugito Sugito; Rusli Rusli; Al Azhar; Abdul Harris (Universitas Syiah Kuala, 2016)
The objective of this study was to examine glucose level in dog's blood before and after hunting activity. This research used 25 local dogs which is kept by Persatuan Olah Raga Buru Babi (PORBI) located at Kenagarian Mungo Sub-district Luak District Kabupaten Lima Puluh Kota West Sumatera. Data were analyzed with T-test. Results showed that average of dog blood glucose level before hunting was 91.56±7.70 mg/dl and significantly decrease (P0.05) to 57.84±5.04 mg/dL after hunting activity. As a conclusion, blood glucose level of dog before hunting activity was found in normal range but lowered glucose level were observed after hunting activity.